Routledge international handbook of cosmopolitanism studies
1 online resource (644 pages)
Keywords: Cosmopolitanism is about the extension of the moral and political horizons of people, societies, organizations and institutions. Over the past 25 years there has been considerable interest in cosmopolitan thought across the human social sciences.The second edition of the Routledge International Handbook of Cosmopolitanism Studiesis an enlarged, revised and updated version of the first edition. It consists of 50 chapters across a broader range of topics in the social and human sciences.Eighteen entirely new chapters cover topics that have become increasingly prominent in cosmopolitan scholarship in recent years, such as sexualities, public space, the Kantian legacy, the commons, internet, generations, care and heritage.This Second Edition aims to showcase some of the most innovative and promising developments in recent writing in the human and social sciences on cosmopolitanism. Both comprehensive and innovative in the topics covered, the Routledge International Handbook of Cosmopolitanism Studies is divided into four sections.Cosmopolitan theory and history with a focus on the classical and contemporary approaches,The cultural dimensions of cosmopolitanism, The politics of cosmopolitanism,World varieties of cosmopolitanism.There is a strong emphasis in interdisciplinarity, with chapters covering contributions in philosophy, history, sociology, anthropology, media studies, international relations. The Handboook’s clear and comprehensive style will appeal to a wide undergraduate and postgraduate audience across the social and human sciences.